Nodo de transformación e investigación a partir del reciclaje (2019)
It proposes to solve the environmental problem of the lack of recycling, through an architecture that instructs, controls and generates a new use for recycling, through the investigation and transformation of new methods of use for architecture generating a social and cultural connection to the region through exhibition areas.